Comparative study between levobupivacaine with clonidine and levobupivacaine with fentanyl in epidural labour analgesia in rural set up - Mishra, Prashant K.; Singh, Anand K.; Divedi, Pragati (International Journal of Research in Medical Sciences, 2017)
Background: Neuraxial techniques are the gold standard for intrapartum labour analgesia. Neuraxial labour analgesia using new local anaesthetics such as levobupivacaine has become very popular by virtue of the safety and lesser motor blockade caused by these agents. Multiple randomized controlled trials comparing epidural analgesia with systemic opioids, nitrous oxide or both have demonstrated lower internal pain scores and higher maternal satisfaction with neuraxial analgesia. The purpose of this study is to compare fentanyl and clonidine combination with levobupivacaine in terms of effect of epidural labour analgesia on fetal outcome and incidence of instrumental or caesarean delivery and duration of second stage of labour. Methods: A total of 50 primiparous with singleton pregnancy and vertex presentation and cervical dilatation of 3-5 cm were enrolled for the study in our hospital in department of obstetrics and gynecology. They were divided into group 1 and group 2 (25 patients in each group). Group 1 received 10 ml. of 0.125% isobaric levobupivacaine with 25µg fentanyl and group 2 received 10 ml of 0.125% isobaric levobupivacaine with 60 µg clonidine. Parturients were given epidural analgesia on numerical rating scale (NRS) Score >3. Breakthrough pain supplemented with 3-5 ml of 0.125% levobupivacaine. Data collected were demographic profile of the patients, analgesic qualities, 1st and 2nd stage labour duration, side effects and feto-maternal outcome. Results: Post treatment mean NRS were almost similar between two groups at all periods except at 15 minutes when it was significantly lower for group 2 (2.64±0.49). Onset of analgesia was earlier in group 2 (13.68±0.94) in comparison to group 1 (15.36±1.18) and was statistically significant. Conclusions: In conclusion Group 2 (levobupivacaine with clonidine) showed significant difference in early onset of analgesia but did not show any significant difference in duration of labour, maternal and fetal outcome and mode of delivery.